2021
DOI: 10.1111/pre.12448
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular characterization of multiple new Azadinium strains revealed a high diversity of non‐toxigenic species of Amphidomataceae (Dinophyceae) including two new Azadinium species in Irish waters, North East Atlantic

Abstract: SUMMARY Shellfish contamination with azaspiracids (AZA), which are lipophilic marine biotoxins produced by marine dinoflagellates, is a major and recurrent problem for the Irish shellfish industry. AZA are produced by certain species of Amphidomataceae, but the species diversity of this group of microalgae in Irish waters is poorly known. Here we present a morphological and molecular characterization of multiple new strains of non‐toxigenic Azadinium isolated on an oceanographic survey in 2018. A lack of AZA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…zhuanum was recently reported from Ireland (Salas et al . 2021). Although the identity of the Irish strain to A. zhuanum is unclear, the present study demonstrated the presence of A. zhuanum also in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…zhuanum was recently reported from Ireland (Salas et al . 2021). Although the identity of the Irish strain to A. zhuanum is unclear, the present study demonstrated the presence of A. zhuanum also in Japan.…”
Section: Discussionmentioning
confidence: 99%